Energy pile space backfilling method based on high thermal conductivity shaped phase change backfill material

By using n-heptadecane and olefin block copolymers to shape the phase change material, combined with graphite powder and block PCM stacking backfill-pore filling method, the existing phase change backfill materials have been solved, and the phase change backfill materials with high thermal conductivity, high latency and structural stability have been achieved, which has improved the thermal conductivity and thermal stability of the energy piles.

CN119775971APending Publication Date: 2025-04-08TAIZHOU HONGYUAN ELECTRIC POWER DESIGN INST CO LTD
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
CN202411655912.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing phase change backfill materials have volatility or loss caused by low heat transfer efficiency, low latent heat, insufficient stability and poor fluidity in energy piles, which affects environmental and structural stability.

Method used

N-heptadecane is used as the phase change material and is shaped by olefin block copolymer, combined with graphite powder to improve thermal conductivity, and a block PCM stacking backfill-pore filling method is used to ensure the compactness and stability of the material.

Benefits of technology

A phase change backfill material with high thermal conductivity, high latent heat and stable is achieved, which improves the thermal conductivity and thermal stability of energy piles, and ensures the structural stability and environmental safety of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775971A_ABST
    Figure CN119775971A_ABST
Patent Text Reader

Abstract

The invention provides an energy pile space backfilling method based on a high thermal conductivity shaped phase change backfill material. n-heptadecane is used as a phase change material, and an olefin block copolymer is used to shape the phase change material to form a stable solid phase change material. The thermal conductivity of the solid phase change material is improved by adding graphite powder. The formed phase change backfill material has high heat transfer effect, high latent heat and good stability. In addition, a suitable amount of liquid n-heptadecane is filled in the block backfill material stacked inside the energy pile structure to ensure that the liquid n-heptadecane can be uniformly filled in the pore structure between the blocks. While ensuring heat conduction and thermal stability, the block material will not be squeezed or damaged due to excessive volume change in the phase change process, thereby ensuring the structural stability of the phase change backfill material. In addition, the material filled in the energy pile has excellent heat conduction and thermal stability and can effectively play a role.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of geothermal development and application technology, and in particular to an energy pile space backfilling method based on high thermal conductivity shaped phase change backfilling material. Background Art

[0002] Shallow geothermal energy, as a renewable clean energy, has been widely used around the world. Energy piles are the structure of the ground source end of ground source heat pumps, which combines the buried heat exchange pipe with the concrete pile foundation of the building. The buried pipe heat exchanger is arranged in the core space of the concrete pile, and the backfill material is used to fill the pores between the buried pipe heat exchanger and the pile to improve the heat exchange efficiency between the buried pipe and the surrounding soil.

[0003] Phase change material is a material with strong heat storage capacity. It can keep constant temperature during phase change and has the advantage of high energy storage density. Using phase change material for backfilling of energy piles can not only increase the heat exchange per unit time between the buried heat exchanger and the surrounding soil during the operation-shutdown cycle, but also reduce the temperature fluctuation of the surrounding soil, reduce the thermal interference of the soil, and accelerate the recovery of the ground temperature of the soil during the intermittent period of the heat exchanger.

[0004] However, the current phase change backfill materials still have problems such as low heat transfer efficiency, low latent heat, and stability that cannot meet the requirements. In addition, when the phase change material is used as a backfill material to directly backfill the energy pile, due to the fluidity of the corresponding liquid material during the solid-liquid phase change process, long-term operation will cause the phase change backfill material to volatilize or lose, which may cause environmental pollution to the local soil, air, etc. Therefore, it is necessary to develop new phase change backfill materials with high thermal conductivity, high latent heat, and good packaging performance.

[0005] At present, most of the phase change materials are encapsulated by porous media adsorption and shaping, or by microcapsules to encapsulate the core phase change materials. This method usually has the problems of low adsorption efficiency, easy leakage during the phase change process, and high prices for microcapsule materials to encapsulate the core phase change materials, which makes it difficult to backfill and apply them in energy piles. In addition, this backfill material with poor fluidity will also have the problem of loose backfill, which leads to the inability of the phase change backfill material to play an effective role and poor structural stability. Summary of the invention

[0006] The purpose of the present invention is to address the deficiencies in the prior art and provide a method for backfilling the space of an energy pile based on a high thermal conductivity shaped phase change backfill material. n-heptadecane is used as a phase change material and fixed, combined with graphite powder, to obtain a phase change backfill material with high heat transfer effect, high latent heat and stability. A new method of block PCM stacking backfilling-pore filling is combined to ensure the structural stability of the phase change backfill material, and the material filled in the energy pile has excellent thermal conductivity and thermal stability, and can effectively play its role.

[0007] According to the purpose of the present invention, there is provided a method for backfilling energy pile space based on high thermal conductivity shaped phase change backfill material, comprising the following steps:

[0008] S1, heating the olefin block copolymer to form a liquid, then adding n-heptadecane, and stirring while maintaining the temperature to obtain a first liquid mixture, continuing to maintain the temperature, adding graphite powder to the first mixture, and continuing to stir evenly to form a second liquid mixture;

[0009] S2, pouring the second liquid mixture obtained in step S1 into a mold of a desired shape, and letting it stand to room temperature after pouring, so that the n-heptadecane containing graphite powder is shaped into a solid state through the olefin block copolymer, and demolding to obtain a plurality of backfill materials with solid block structures;

[0010] S3, transporting the backfill materials of the solid block structure obtained in step S2 into the energy pile one by one to form a stack until the backfill materials are piled up to the top of the energy pile;

[0011] S4, using liquid n-heptadecane to backfill the inside of the energy pile treated in step S3, filling the pores between the stacked backfill materials, ensuring the compactness of the backfill materials, and then ensuring the heat transfer performance and stability of the backfill materials; wherein, according to the pore volume V of the stacked backfill materials in the energy pile pores , and the volume V of liquid n-heptadecane when it undergoes maximum phase change expansion expanded Obtain the backfill volume V of liquid n-heptadecane liquid .

[0012] As an optional embodiment, the pore volume V of the backfill material in the energy pile after stacking pores , and the volume V of liquid n-heptadecane when it undergoes maximum phase change expansion expanded Obtain the estimated backfill volume V of liquid n-heptadecane liquid ,include:

[0013] According to the internal space volume V of the energy pile and the total volume V of the stacked backfill material block , calculate the pore volume V pores ;

[0014] According to the estimated backfill volume V of liquid n-heptadecane liquid , the phase change expansion coefficient ɑ of liquid n-heptadecane, and the maximum temperature change range ΔT of liquid n-heptadecane, calculate the volume V of liquid n-heptadecane when the maximum phase change expansion occurs expanded ;

[0015] According to V expanded and V pores , and obtain the backfill volume V of liquid n-heptadecane liquid The upper limit of

[0016] According to the initial formation of a continuous heat conduction path, the backfill volume V of liquid n-heptadecane is obtained. liquid The lower limit of .

[0017] As an optional embodiment, the internal space volume V of the energy pile and the total volume V of the stacked backfill material are block , calculate the pore volume V pores , determined according to formula (1):

[0018] V pores =VV block (1).

[0019] As an optional embodiment, the backfill volume V1 of the estimated liquid n-heptadecane is iquid , the phase change expansion coefficient ɑ of liquid n-heptadecane, and the maximum temperature change range ΔT of liquid n-heptadecane, calculate the volume V of liquid n-heptadecane when the maximum phase change expansion occurs expanded , determined according to formula (2):

[0020] V expanded =V liquid (1+ɑΔT) (2)

[0021] In the formula, the value range of ɑ is 0.05~0.1, and the value of ΔT is 10~15.

[0022] As an optional embodiment, according to V expanded and V pores , and obtain the backfill volume V of liquid n-heptadecane liquid The upper limit includes:

[0023] When V expanded Equal to V pores When V liquid The value is the backfill volume V of liquid n-heptadecane liquid upper limit.

[0024] As an optional embodiment, the backfill volume V of the liquid n-heptadecane is obtained according to the initial formation of the continuous heat conduction path. liquid The lower limit includes:

[0025] Backfill volume V of liquid n-heptadecane liquid The lower limit is (20% to 30%)V pores .

[0026] As an optional embodiment, the mass ratio of n-heptadecane to the olefin block copolymer is (8:2) to (9:1).

[0027] As an optional implementation, the added amount of graphite powder is 5% to 10% of the mass of the first liquid mixture.

[0028] As an optional embodiment, the olefin block copolymer is formed by extrusion of hard segments and soft segments of ethylene-octene.

[0029] As an optional implementation, the particle size of the graphite powder ranges from 1800 mesh to 8000 mesh.

[0030] It can be seen from the above technical scheme of the present invention that the energy pile space backfilling method based on high thermal conductivity shaped phase change backfill material proposed by the present invention adopts n-heptadecane as the phase change material, and adopts olefin block copolymer to shape it to form a stable solid phase change material, and improves the thermal conductivity of the solid phase change material by adding graphite powder. The formed phase change backfill material has high heat transfer effect, high latent heat and good stability, and by filling a suitable amount of liquid n-heptadecane in the block backfill material stacked inside the energy pile structure, it is ensured that the liquid n-heptadecane can be evenly filled in the pore structure between the blocks. While ensuring thermal conduction and thermal stability, the block material will not be squeezed or damaged due to excessive volume changes in the phase change process, thereby ensuring the structural stability of the phase change backfill material, and the material filled in the energy pile has excellent thermal conduction and thermal stability, and can effectively play its role.

[0031] The energy pile space backfilling method based on the high thermal conductivity fixed phase change backfill material of the present invention is relatively simple, has low preparation cost, short preparation cycle, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a flow chart of the energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material of the present invention.

[0033] Figure 2 It is a schematic diagram of an olefin block copolymer-shaped phase change material, wherein Figure A is a block structure diagram of an olefin block copolymer, and Figure B is a micelle structure formed by the olefin block copolymer-shaped phase change material.

[0034] Figure 3 : is the DSC differential scanning calorimetry curve of the backfill material with solid block structure in the embodiment of the present invention. DETAILED DESCRIPTION

[0035] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.

[0036] Various aspects of the present invention are described in this disclosure with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the present disclosure are not necessarily intended to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways.

[0037] Combination Figure 1 As shown, in an exemplary embodiment of the present invention, a method for backfilling energy pile space based on high thermal conductivity shaped phase change backfill material is provided, comprising the following steps:

[0038] S1, heating the olefin block copolymer to form a liquid, then adding n-heptadecane, and stirring while maintaining the temperature to obtain a first liquid mixture, continuing to maintain the temperature, adding graphite powder to the first mixture, and continuing to stir evenly to form a second liquid mixture;

[0039] S2, pouring the second liquid mixture obtained in step S1 into a mold of a desired shape, and letting it stand to room temperature after pouring, so that the n-heptadecane containing graphite powder is shaped into a solid state through the olefin block copolymer, and demolding to obtain a plurality of backfill materials with solid block structures;

[0040] S3, transporting the backfill materials of the solid block structure obtained in step S2 into the energy pile one by one to form a stack until the backfill materials are piled up to the top of the energy pile;

[0041] S4, using liquid n-heptadecane to backfill the inside of the energy pile treated in step S3, filling the pores between the stacked backfill materials, ensuring the compactness of the backfill materials, and then ensuring the heat transfer performance and stability of the backfill materials; wherein, according to the pore volume V of the stacked backfill materials in the energy pile pores , and the volume V of liquid n-heptadecane when it undergoes maximum phase change expansion expanded Obtain the backfill volume V of liquid n-heptadecane liquid .

[0042] As an optional example, according to the pore volume V of the backfill material after stacking in the energy pile pores , and the volume V of liquid n-heptadecane when it undergoes maximum phase change expansion expanded Obtain the estimated backfill volume V of liquid n-heptadecaneliquid ,include:

[0043] According to the internal space volume V of the energy pile and the total volume V of the stacked backfill material block , calculate the pore volume V pores ;

[0044] According to the estimated backfill volume V of liquid n-heptadecane liquid , the phase change expansion coefficient ɑ of liquid n-heptadecane, and the maximum temperature change range ΔT of liquid n-heptadecane, calculate the volume V of liquid n-heptadecane when the maximum phase change expansion occurs expanded ;

[0045] According to V expanded and V pores , and obtain the backfill volume V of liquid n-heptadecane liquid The upper limit of

[0046] According to the initial formation of a continuous heat conduction path, the backfill volume V of liquid n-heptadecane is obtained. liquid The lower limit of .

[0047] As an optional example, according to the internal space volume V of the energy pile and the total volume V of the backfill material that has been stacked block , calculate the pore volume V pores , determined according to formula (1):

[0048] V pores =VV block (1).

[0049] As an optional example, the backfill volume V1 of the estimated liquid n-heptadecane is iquid , the phase change expansion coefficient ɑ of liquid n-heptadecane, and the maximum temperature change range ΔT of liquid n-heptadecane, calculate the volume V of liquid n-heptadecane when the maximum phase change expansion occurs expanded , determined according to formula (2):

[0050] V expanded =V liquid (1+ɑΔT) (2)

[0051] In the formula, the value range of ɑ is 0.05~0.1, and the value of ΔT is 10~15.

[0052] According to existing literature, similar long-chain alkanes usually have a volume change rate of about 5% to 10% during a solid-liquid phase transition; for example, n-hexadecane has a volume shrinkage rate of about 8% during a liquid-solid phase transition. Therefore, in a preferred example, the phase change expansion coefficient of n-heptadecane is 0.08. It is understandable that in actual applications, those skilled in the art can further determine the phase change expansion coefficient of n-heptadecane through experimental measurements based on actual conditions.

[0053] For specific backfill application scenarios such as energy piles, the temperature range of liquid n-heptadecane will be limited by the thermal stability of the system; in most areas, the annual fluctuation range of shallow underground temperature (generally at a depth of 10 to 20 meters) is about 10 to 25°C. In order to enable n-heptadecane to effectively undergo phase change in this geothermal environment, its optimal temperature range can be set to 15 to 25°C, and the phase change temperature of n-heptadecane is between 22 and 24°C. This ensures that n-heptadecane is in liquid state most of the time and can absorb or release heat in time according to changes in ground temperature; therefore, a ΔT value of 10 to 15 basically meets the requirements of most energy piles, and can be preferably 10; it can be understood that in actual application, technical personnel in this field can also select a suitable ΔT according to the actual environment.

[0054] As an optional example, according to V expanded and V pores , and obtain the backfill volume V of liquid n-heptadecane liquid The upper limit includes:

[0055] When V expanded Equal to V pores When V liquid The value is the backfill volume V of liquid n-heptadecane liquid upper limit.

[0056] As an optional example, according to the initial formation of a continuous heat conduction path, the backfill volume V of the liquid n-heptadecane is obtained. liquid The lower limit includes:

[0057] Backfill volume V of liquid n-heptadecane liquid The lower limit is (20% to 30%)V pores ; At this point, a preliminary continuous heat conduction path can begin to form.

[0058] As an optional example, the mass ratio of n-heptadecane to the olefin block copolymer is (8:2) to (9:1), and is particularly preferably 8:2.

[0059] As an optional example, the added amount of graphite powder is 5% to 10% of the mass of the first liquid mixture, and is particularly preferably 5%.

[0060] As an optional example, the olefin block copolymer is formed by extrusion of hard segment and soft segment of ethylene-octene, such as the hydrocarbon block copolymer (OBC for short) branded as OBC9900 produced by Dow Chemical Company of the United States.

[0061] Olefin block copolymers are formed by the interlocking of "hard segment" and "soft segment" structures. They have high toughness and elastic plasticity and can well withstand the volume expansion and contraction of phase change materials during solid-liquid phase change. Compared with conventional porous medium adsorption materials, this type of shaping material can make the phase change material well fixed inside the structure, and it is not easy to leak after long-term use. The phase change material is completely wrapped in the skeleton structure, such as Figure 2 As shown, the olefin block copolymer fixes the phase change material to form a micellar structure. This stable structure makes the phase change process appear as a solid-solid phase change on a macro scale, and the price is relatively low. In addition, compared with other porous structured adsorbent materials or microcapsule-shaped materials formed by core-shell encapsulation, the preparation process of this olefin block copolymer-shaped adsorbent phase change material is simpler, without the need for extremely high temperature and vacuum adsorption and other more complicated preparation processes, and without the need to emulsify the phase change material and then encapsulate the shell structure to form a microcapsule material. However, the traditional porous adsorption shaping material also has a low adsorption rate, and most of the microcapsule encapsulation phase change material processes also have the problem of low encapsulation rate, and the encapsulation rate is usually less than 50%, and during the phase change process, due to the change in solid-liquid volume, the phase change material expands in volume and squeezes out the shaped adsorbent material, or crushes the microcapsule shell structure, resulting in leakage of the phase change material. Long-term reciprocating use will inevitably lead to the decline of its functionality, greatly shortening its service life.

[0062] Due to its good toughness and elastic-plasticity, olefin block copolymers can effectively inhibit material leakage and other problems caused by volume expansion of phase change materials during the solid-liquid phase change process. The use of olefin block copolymers for shaping adsorption can greatly improve the production and preparation efficiency of this phase change material, ensuring that the adsorption rate of the phase change material is close to 100%, saving production costs, simplifying production processes, improving the adsorption efficiency of phase change materials and extending service life.

[0063] As an optional example, the particle size of the graphite powder ranges from 1800 mesh to 8000 mesh.

[0064] As an alternative example, the purity of n-heptadecane is 99%.

[0065] As an optional example, the olefin block copolymer is heated to 140-180° C. to form a liquid state, and maintained at a temperature of 140-180° C. until a second liquid mixture is obtained.

[0066] As an optional example, after adding n-heptadecane to the liquid olefin block copolymer, stirring is performed at a rotation speed of 500 to 1000 rpm for at least 60 minutes to obtain a first liquid mixture.

[0067] As an optional example, graphite powder is added to the first mixture, and the mixture is stirred at a rotation speed of more than 1500 rpm for at least 60 minutes to form a second liquid mixture.

[0068] It can be understood that, in order to facilitate calculation, the backfill material of the solid block structure can be arranged into a regular cubic structure, so that the backfill material of the solid block structure forms a face-centered cubic close stacking in the energy pile space.

[0069] For better understanding, the present invention is further described below in conjunction with several specific examples, but the preparation process is not limited thereto, and the content of the present invention is not limited thereto.

[0070] Unless otherwise specified, the materials in the examples were prepared according to existing methods or directly purchased from the market.

[0071] Example 1

[0072] The mass ratio of C17 and OBC was selected to be 8:2. First, OBC was heated to 160°C to form liquid OBC, and then C17 was added to form a liquid blend. The heating temperature was maintained at 160°C, and it was stirred at high speed at high temperature. The stirring speed was set at 1000r / min and the stirring time was 60min. Then, the temperature was maintained at 160°C, and graphite powder with a mass fraction of 5% was added thereto. The speed was increased to 1500r / min, and the mixture was stirred at high speed for 60min to obtain a liquid mixture.

[0073] The formed liquid mixture is poured into a cubic mold (with a side length of 0.1 m). After the pouring is completed, it is allowed to stand at room temperature to allow the n-heptadecane containing graphite powder to be shaped into a solid state through the olefin block copolymer. The mold is then demolded to obtain a number of backfill materials with solid block structures.

[0074] The solid block-shaped backfill materials are transported one by one into the energy pile (the internal space is a cylinder with a bottom radius of 1m and a height of 5m) to form a stack until the backfill materials are piled up to the top of the energy pile. A total of 7,854 solid block backfill materials have been placed.

[0075] Calculate the backfill volume V of liquid n-heptadecane liquid :

[0076] V pores =VV block =5π-7854×0.1 3 =7.856m 3

[0077] V expanded =V liquid (1+ɑΔT)=V liquid (1+0.08×10)=7.856

[0078] V liquid The upper limit is 4.36m 3

[0079] V liquid The lower limit is 20% V pores =1.57m 3

[0080] In order to ensure good heat conduction and enable the backfill material to effectively absorb and release heat during the phase change process, V liquid The upper limit value of is taken as the backfill volume of liquid n-heptadecane.

[0081] Using 4.36m 3 The liquid n-heptadecane is backfilled into the interior of the energy pile stacked with the solid block-structured backfill material, thus completing the backfilling of the energy pile space.

[0082] Example 2

[0083] The backfill material with solid block structure obtained in Example 1 was subjected to DSC analysis, and the results were as follows: Figure 3 shown.

[0084] As can be seen from the figure, the phase change starting temperature of the phase change material is 24.9°C, the peak value is 29.6°C, the phase change ending temperature is 38.4°C, and the phase change latent heat reaches 144.7 J / g.

[0085] Measured by a thermal conductivity tester, the thermal conductivity of the material can reach above 1.25W / (m·K).

[0086] Therefore, it can be proved that the material of the present invention is used for backfilling of energy piles, and can release or absorb latent heat through phase change to alleviate the temperature change amplitude around the buried pipe, shorten the distance between the buried pipes, and improve the heat exchange efficiency, so as to improve the heat exchange per unit time of the buried pipe during the extraction of geothermal energy in summer, reduce the fluctuation of the surrounding soil, and improve the thermal conductivity between the buried pipe and the surrounding soil, and has good stability and low maintenance cost; combined with a suitable amount of liquid n-heptadecane, it is evenly filled in the pore structure between the blocks, while ensuring heat conduction and thermal stability, it will not cause extrusion and other damage to the block material due to excessive volume change in the phase change process, thereby ensuring the structural stability of the phase change backfill material, and the material filled in the energy pile has excellent thermal conductivity and thermal stability, and can effectively play its role.

[0087] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.

Claims

1. A method for backfilling energy pile space based on high thermal conductivity shaped phase change backfill material, characterized in that: The following steps are involved: S1, heating the olefin block copolymer to form a liquid, then adding n-heptadecane, and stirring while maintaining the temperature to obtain a first liquid mixture, continuing to maintain the temperature, adding graphite powder to the first mixture, and continuing to stir evenly to form a second liquid mixture; S2, pouring the second liquid mixture obtained in step S1 into a mold of a desired shape, and letting it stand to room temperature after pouring, so that the n-heptadecane containing graphite powder is shaped into a solid state through the olefin block copolymer, and demolding to obtain a plurality of backfill materials with solid block structures; S3, transporting the backfill materials of the solid block structure obtained in step S2 into the energy pile one by one to form a stack until the backfill materials are piled up to the top of the energy pile; S4, using liquid n-heptadecane to backfill the inside of the energy pile treated in step S3, filling the pores between the stacked backfill materials, ensuring the compactness of the backfill materials, and then ensuring the heat transfer performance and stability of the backfill materials; wherein, according to the pore volume V of the stacked backfill materials in the energy pile pores , and the volume V of liquid n-heptadecane when it undergoes maximum phase change expansion expanded Obtain the backfill volume V of liquid n-heptadecane liquid .

2. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 1 is characterized in that: The pore volume V of the backfill material after stacking in the energy pile pores , and the volume V of liquid n-heptadecane when it undergoes maximum phase change expansion expanded Obtain the estimated backfill volume V of liquid n-heptadecane liquid ,include: According to the internal space volume V of the energy pile and the total volume V of the stacked backfill material block , calculate the pore volume V pores ; According to the estimated backfill volume V of liquid n-heptadecane liquid , the phase change expansion coefficient ɑ of liquid n-heptadecane, and the maximum temperature change range ΔT of liquid n-heptadecane, calculate the volume V of liquid n-heptadecane when the maximum phase change expansion occurs expanded ; According to V expanded and V pores , and obtain the backfill volume V of liquid n-heptadecane liquid The upper limit of According to the initial formation of a continuous heat conduction path, the backfill volume V of liquid n-heptadecane is obtained. liquid The lower limit of .

3. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 2 is characterized in that: The internal space volume V of the energy pile and the total volume V of the stacked backfill material block , calculate the pore volume V pores , determined according to formula (1): V pores =VV block (1)。 4. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 2 is characterized in that: The backfill volume V1 of the estimated liquid n-heptadecane iquid , the phase change expansion coefficient ɑ of liquid n-heptadecane, and the maximum temperature change range ΔT of liquid n-heptadecane, calculate the volume V of liquid n-heptadecane when the maximum phase change expansion occurs expanded , determined according to formula (2): V expanded =V liquid (1+ɑΔT) (2) In the formula, the value range of ɑ is 0.05~0.1, and the value of ΔT is 10~15.

5. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 2 is characterized in that: According to V expanded and V pores , and obtain the backfill volume V of liquid n-heptadecane liquid The upper limit includes: When V expanded Equal to V pores When V liquid The value is the backfill volume V of liquid n-heptadecane liquid upper limit.

6. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 2 is characterized in that: The initial continuous heat conduction path is formed according to the method, and the backfill volume V of the liquid n-heptadecane is obtained. liquid The lower limit includes: Backfill volume V of liquid n-heptadecane liquid The lower limit is (20% to 30%)V pores .

7. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 1 is characterized in that: The mass ratio of n-heptadecane to olefin block copolymer is (8:2) to (9:1).

8. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 1 is characterized in that: The added amount of graphite powder is 5% to 10% of the mass of the first liquid mixture.

9. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 1 is characterized in that: The olefin block copolymer is formed by extrusion of hard segments and soft segments of ethylene-octene.

10. The energy pile space backfilling method based on high thermal conductivity fixed phase change backfill material according to claim 1 is characterized in that: The particle size of the graphite powder ranges from 1800 mesh to 8000 mesh.